2016
DOI: 10.7150/ijms.14056
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Peritoneal Surface as a Decisive Factor for Intestinal Adhesions in Intraperitoneal Onlay Mesh Surgery - Introducing a New Rat Model

Abstract: Background: Meshes implanted intraperitoneally are known to cause adhesions potentially resulting in complications such as chronic pain, enterocutaneous fistula, or mesh infection. This study introduces a model for investigation of intestine-to-mesh adhesions and evaluates as to whether missing of visceral peritoneum is causative.Methods: In 18 rats, rectangular 1.5 x 2 cm patches of an uncoated polypropylene mesh (Ultrapro®) were sewn to the inner abdominal wall next to the cecum. Additionally, a meso-suture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Recent studies showed that not only the foreign material or making of mesh but also the impairment of visceral peritoneum is a co-decisive factor for the development of intestine-to-mesh adhesions 18, 25, 26. This especially accounts for areas where intestine has been dissected from the hernia sac.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Recent studies showed that not only the foreign material or making of mesh but also the impairment of visceral peritoneum is a co-decisive factor for the development of intestine-to-mesh adhesions 18, 25, 26. This especially accounts for areas where intestine has been dissected from the hernia sac.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study our recently described rat model was used 18. General anaesthesia was achieved by intraperitoneal injection of 80 mg/kg body weight ketamine and 5 mg/kg xylazine.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations